1810 R.I. Pub. Laws 52 - (:unkn) unknown (My University, 1798)
An Act Relative To The Keeping Gun-Powder In The Town Of Providence, §2: That no person or persons shall hereafter keep or deposit gunpowder, in a greater quantity than twenty-eight pounds, in any shop, building or other place, in the town of Providence, except such place or places as the Town Council of said town shall allow and designate for that purpose.
Keywords: GUNPOWDER - STORAGE